Beta-2-microglobulin Mutations Are Linked to a Distinct Metastatic Pattern and a Favorable Outcome in Microsatellite-Unstable Stage IV Gastrointestinal Cancers - Busch, Elena; Ahadova, Aysel; Kosmalla, Kosima; Bohaumilitzky, Lena; Pfuderer, Pauline L.; Ballhausen, Alexej; Witt, Johannes; Wittemann, Jan-Niklas; Bläker, Hendrik; Holinski-Feder, Elke; Jäger, Dirk; von Knebel Doeberitz, Magnus; et al. (Frontiers in Oncology, 2021)
Immune checkpoint blockade (ICB) shows remarkable clinical effects in patients with metastatic microsatellite-unstable (MSI) cancer. However, markers identifying potential non-responders are missing. We examined the prevalence of Beta-2-microglobulin (B2M) mutations, a common immune evasion mechanism, in stage IV MSI gastrointestinal cancer and its influence on metastatic pattern and patients’ survival under ICB. Twenty-five patients with metastatic, MSI gastrointestinal adenocarcinoma were included. Eighteen patients underwent ICB with pembrolizumab and one patient with nivolumab/ipilimumab. Sequencing was performed to determine B2M mutation status. B2M mutations and loss of B2M expression were detected in 6 out of 25 stage IV MSI cancers. B2M mutations were strongly associated with exclusively peritoneal metastasis (p=0.0312). However, no significant differences in therapy response (25% vs. 46.6%, p>0.99) and survival (median PFS: 19.5 vs 33.0 months, p=0.74; median OS 39 months vs. not reached, p>0.99) were observed between B2M-mutant and B2M-wild type tumor patients. Among metastatic MSI GI cancers, B2M-mutant tumors represent a biologically distinct disease with distinct metastatic patterns. To assess ICB response in B2M-mutant MSI cancer patients, future studies need to account for the fact that baseline survival of patients with B2M-mutant MSI cancer may be longer than of patients with B2M-wild type MSI cancer.